Project Based Learning untuk Meningkatkan Hasil Belajar English for Specific Purposes: Sebuah Penelitian Tindakan - Yuana Liverita Goodianti; Ihtiara Fitrianingsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
While the ability to communicate in English according to majors, to collaborate, and to be creative is urgently required by vocational high school (SMK) graduates, in reality, students’ English language skills for this major are still low, around 67.74% or 21 students stated that speaking was an obstacle. Therefore, through Project Based learning (PjBL), this research was carried out to improve learning outcomes of English for Specific Purposes and determine the improvement of learning outcomes of English for Specific Purposes. The classroom action research, with the stages of planning, implementing, observing and reflecting on actions, was conducted at SMK N 2 Wonosari through two cycles (8 meetings) involving 36 DKV students in grade X. The teacher acted as the prominent researcher and was assisted by an observer. Data were collected using tests, observation sheets, and product assessment sheets. Data analysis was carried out by comparing the results of Cycle I and II quantitatively, while observation data were investigated qualitatively. The results suggest that Project Based Learning is likely effective in improving DKV students’ learning outcomes in ESP. In terms of process, students perceive that their learning improved from 67% up to 100%, and the implementation of PjBL as assessed by the teacher, likewise rose by 17.67. Notable improvement was also apparent in students’ test results, rising from 69.44% to 100% in cycle II, with and 80% of them hitting the score of 80. Conclusively, PjBL can be an alternative endeavor to create meaningful experiences in collaboration, creativity, communication skills and technology-based product presentations.